Nigella sativa Oil Alleviates Mouse Testis and Sperm Abnormalities Induced by BPA Potentially through Redox Homeostasis - Al-Griw, Mohamed A.; Shalabi, Suliman M.; Alghazeer, Rabia O.; Elnfati, Abdul H.; Treesh, Soad A.; Benjama, Ahmeda E.; Shamlan, Ghalia; Habibullah, Mahmmoud M.; Eskandrani, Areej A.; Alnajeebi, Afnan M.; Babteen, Nouf A.; Alansari, Wafa S. (Combinatorial Chemistry & High Throughput Screening, 2023)
Background & Aim: Significant evidence indicates that endocrine disrupted bisphenol A (BPA) seriously endangers human health. In males, BPA affects testis architecture and sperm quality, and ultimately reduces fertility. This study explored the therapeutic potential of Nigella sativa (NS) seed extract on testis and sperm abnormalities in BPA-exposed mice and characterized the underlying mechanism. Methods: Forty male Swiss albino mice (5.5 weeks old, N = 8 per group) were randomly divided into five groups: Group I, normal control, Group II, vehicle control (sterile corn oil); Group III, NS-exposed (oral 200 mg/kg); Group IV, BPA-exposed (oral 400 μg/kg body weight); Group V, BPA + NS-exposed mice. Animals were treated for 6 weeks and sacrificed for biochemical and histological examination. Results: The results indicated that BPA exposure results in significant testis and sperm abnormalities. Specifically, BPA promoted a marked reduction in the body and testis compared with the control group. Histopathological findings showed that BPA caused a widespread degeneration of spermatogenic cells of the seminiferous epithelium, decreased sperm counts and motility, and augmented sperm abnormalities, and whereas little alteration to sperm DNA was observed. In addition, BPA increased the levels of the lipid peroxidation marker, malondialdehyde (MDA), and reduced the levels of the antioxidant marker, reducing glutathione (GSH). Treatment with NS oil extract during BPA exposure significantly alleviated testis and sperm abnormalities, reduced MDA levels, and enhanced GSH levels. Conclusion: The results demonstrate that NS oil protects mice against BPA-induced sperm and testis abnormalities, likely by suppressing levels of the oxidative stress marker, MDA, and enhancing the levels of the antioxidant marker, GSH.
Keywords: reproductive toxicity